ON D-OPTIMAL CHEMICAL BALANCE WEIGHING DESIGNS - Ceranka, Bronisław; Graczyk, Małgorzata (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The paper deals with the problem of determining the chemical balance weighing designs satisfying the criterion of D-optimality under assumption that the measurement errors are equal correlated and they have the same variances. The existence conditions and the form of the optimal design are given. Moreover, some construction methods of the design matrices based on the incidence matrices of the balanced incomplete block designs and ternary balanced block designs are presented. Any example of construction is given.